KRITIK ATAS GAYA HIDUP HEDONISME DALAM PERSPEKTIF ETIKA PESIMISME ARTHUR SCHOPENHAUER - Siswadi, Gede Agus; Puspadewi, I Dewa Ayu; Violita, Michella Desri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Hedonism is a view that prioritizes the pursuit of happiness and pleasure as the main goal in life. While this concept is appealing to some, it is not without its critics. Hedonism is often criticized as leading to a less meaningful life. If the only goal is to seek pleasure and avoid suffering, then it can neglect the deeper and more meaningful aspects of life, such as devotion to others, and the development of ethics and morality. One criticism of the hedonistic lifestyle comes from the thoughts of Arthur Schopenhauer. Therefore, with a qualitative method and a philosophical hermeneutic approach, the results of this study show that Arthur Schopenhauer views life as a series of sufferings, humans suffer because of their will. The effort in finding happiness in Schopenhauer's view is to control the will. Happiness cannot be measured in terms of physical pleasures such as food, drink, or entertainment and luxury goods. However, true happiness arises from asceticism and the denial of the will. The hedonistic lifestyle for Schopenhauer is a futile behavior, because it actually brings humans to the brink of suffering.